Analisis Dampak Perilaku Minum Tuak/Thockh Pada Remaja Usia 12-18 Tahun Di Desa Kaera Padangsul Alor-NTT - Wilianus Illu; Sulaiman Sulaiman; Olivia Masihoru (Missio Ecclesiae, 2023)
Tuak/thockh is an alcoholic drink in the village of Kaera-Padangsul. Tuak is believed by the Padangsul people to be a heritage from their ancestors that must be preserved. The aim of this research is to determine the causes and impacts of consuming alcoholic drinks such as palm wine by teenagers aged 12-18 years. This research uses a qualitative-descriptive method which is carried out by researchers, through and within the method steps. One of them is that the researcher conducted field research in mid-September-October 2023. The researcher conducted in-depth observations and interviews with 5 (five) informants. Researchers found results that show that the main problem in teenagers aged 12-18 years consuming palm wine is caused by family/parental, cultural, economic, social, health, educational and spiritual factors. This has a significant impact on their education, namely they do not continue their education (drop out of school). Damages physical health such as coughing up blood, lung disease. Fights with friends, even with his biological parents, has no self-confidence, talks a lot, is lazy at work. Don't pray, don't go to places of worship, and don't read the holy books. Starting from this basis, all elements within the Kaera Padangsul village community need to network and work together to assist in the development of teenagers aged 12-18 years, so that the future of teenagers at that age can be achieved in accordance with their dreams and their lives. will be better and more prosperous.